Freeze-dried herbal Kaempferia galanga supplementation effectively modulates hyperglycemia-induced oxidative stress and apoptosis in diabetic BALB/c mice - Flavius Phrangsngi Nonglang; Revelbornstar Snaitang; Dhritiman Roy; Surya Bhan (Future Journal of Pharmaceutical Sciences)
Abstract Background A dysfunction in insulin secretion or action leads to hyperglycemia. Hyperglycemia then causes the activation of pathways that result in increased production of reactive oxygen and nitrogen species (ROS/RNS) levels, ultimately causing oxidative stress. Oxidative stress overload then causes cellular damage and also promotes the increased activation of the apoptosis pathway inducing cell death. Thus, regulation of glucose homeostasis to prevent hyperglycemia is crucial. In this study, the potential protective effect of Kaempferia galanga herbal extract (KGE) on hyperglycemia-induced oxidative stress and apoptosis was investigated. Result In this study, Kaempferia galanga (KG) herbal extracts, namely aqueous (KGA), ethanolic (KGE), methanolic (KGM), and chloroform (KGC), were tested for their antioxidant activity. In in vitro antioxidant assays, KG ethanolic extract (KGE) has the highest antioxidant activity out of all the extracts. High-performance thin layer chromatography phytochemical fingerprinting (HPTLC) analysis confirms that the presence of more antioxidant compounds in herbal KGE and ethyl-p methoxy cinnamate (EPMC) was the active phytochemical. Thus, KGE was chosen for in vivo studies. An intraperitoneal streptozotocin (STZ) administration produced a diabetic mouse model. In vivo herbal KGE treatment positively modulates SOD and CAT gene and protein expression in diabetic mice. Tissue protection from herbal KGE supplementation is supported by liver electron microscopy. In diabetic mice, herbal KGE supplementation reduces DNA fragmentation in the liver, kidney, pancreas, and heart by upregulating the gene and protein expression of anti-apoptotic BCL-2, inhibiting BAX expression, and ultimately inhibiting caspase-3 (CAS-3) expression. Herbal KGE supplementation in diabetic mice maintains insulin levels in serum and pancreas, indicating its protective role in preventing pancreatic damage or promoting β cell regeneration. Molecular docking analysis shows EPMC's high binding affinity for CAS-3, BAX, and BCL-2 compared to metformin suggesting that it may be responsible for modulating apoptotic protein expression. Discussion Herbal KGE supplementation protects against diabetes-induced tissue damage and apoptosis by reducing hyperglycemia-induced oxidative stress and apoptosis, and EPMC may be the active component eliciting the effect.